Chapter 9 Medicine and Improvement in the Scots Magazine; and Edinburgh Literary Miscellany (1804-17) - Megan Coyer (Taylor & Francis, 2018)
In this chapter I examine how Archibald Constable's Scots Magazine; and Edinburgh Literary Miscellany (1804-17) became a medium for the promotion of key medical initiatives in early nineteenth-century Edinburgh, including the campaign for the Edinburgh Lunatic Asylum, but also other medico- philanthropic endeavours directed towards improving health in Scotland.